2018
DOI: 10.1186/s12870-018-1393-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exogenous calcium on cucumber fruit quality, photosynthesis, chlorophyll fluorescence, and fast chlorophyll fluorescence during the fruiting period under hypoxic stress

Abstract: BackgroundPlants often suffer from hypoxic stress during waterlogging and hydroponic culturing. This study investigated the response of cucumber (Cucumis sativus L.) plant growth parameters, leaf photosynthesis, chlorophyll fluorescence, fast chlorophyll a fluorescence transient (OJIP), and fruit quality parameters to hypoxic stress alleviated by exogenous calcium. During the fruiting period, cucumber plants were exposed to hypoxia and hypoxia + Ca2+ treatment (4 mM Ca2+) for 9 d.ResultExogenous calcium applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
46
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 41 publications
12
46
3
2
Order By: Relevance
“…According to Figure 3, the chlorophyll contents in CaCl 2 -treated peppers were the most comparing other treatments during storage. He et al [30] also found that CaCl 2 treatment reduced the hypoxic damage of cucumber leaves and enhanced the stability of chlorophylls. However, HT and HT-CaCl 2 treatments were related to temperature, and chlorophylls are sensitive to temperature, which accelerated chlorophylls degradation in some extent.…”
Section: Water Relaxation Timementioning
confidence: 94%
“…According to Figure 3, the chlorophyll contents in CaCl 2 -treated peppers were the most comparing other treatments during storage. He et al [30] also found that CaCl 2 treatment reduced the hypoxic damage of cucumber leaves and enhanced the stability of chlorophylls. However, HT and HT-CaCl 2 treatments were related to temperature, and chlorophylls are sensitive to temperature, which accelerated chlorophylls degradation in some extent.…”
Section: Water Relaxation Timementioning
confidence: 94%
“…Calcium, an essential element for plants, serves not only as a structural component in plant cells but also as a key signaling molecule involved in multiple signal-transduction pathways in its ionic form Ca 2+ (White and Broadley, 2003;Tian et al, 2019). In particular, calcium has well-documented roles in mediating plant responses to abiotic and biotic stimuli (Cachorro et al, 1994;Skórzyńska-Polit et al, 1998;White and Broadley, 2003;Ding et al, 2018;He et al, 2018;Naeem et al, 2018;Patrick et al, 2018). Low-temperature stress often leads to an increase in free Ca 2+ in plants, followed by cold-induced protein phosphorylation and the accumulation of the cold acclimationspecific genes that improve the adaptation of plants to cold stress (Monroy and Dhindsa, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Kallestad et al [25] also found similar effects in pecan tree (Carya illinoinensis) seedlings. On the other hand, chlorophyll fluorescence parameters have been widely used as indicators of the photosystem II (PSII) activity under soil oxygen deficiency conditions [26,27]. Ren et al [23] found a reduction of 16% in the F v /F m and Y (II) values in two maize (Zea mays L.) hybrids under short waterlogging periods (6 d).…”
Section: Introductionmentioning
confidence: 99%